Experiences Supporting Local Health Departments to Increase Human Papillomavirus Vaccination Rates. Issue 3 (May 2016) - Drezner, Kate; Heyer, Kate P.; McKeown, Lisa; Kan, Lilly
Abstract : This article describes experiences supporting local health departments to increase HPV vaccination rates.